Método HERVAT en el aprendizaje de Matemática en estudiantes del tercer año paralelo “B”, Unidad Educativa “José Ángel Palacio”, periodo 2023-2024 - Briceño Santorun, Angie Daniela (2024)
The HERVAT method is consolidated as a very useful tool in the educational field as it is directly based on neuroscience and applied neuroeducation, with a holistic approach has proven to be effective in the learning of Mathematics and widely used in other educational environments, it provides a deeper and more meaningful understanding of pedagogical practices, this research had as general objective: Determine the influence of the application of the HERVAT method in the learning process of Mathematics in the students of the third year parallel "B" in the Educational Unit "José Ángel Palacio" period 2023-2024; as first specific objective: Identify the level of learning of Mathematics in the students of the third year within their academic formation; the second was: Design a program of learning activities based on the HERVAT methodology to improve the learning of Mathematics and the third was: To verify the efficiency of the didactic guide in the learning of Mathematics and the academic performance of the students before and after the application of the HERVAT method; the methodology implemented was a mixed approach that is to say, quantitative- qualitative of quasi-experimental design; during the research the descriptive, statistical and analytical methods were applied, the techniques used were direct observation, interview, and the pre-post evaluation questionnaire, there was a population of 21 students and a teacher of the third year parallel "B" thanks to the help of non-probabilistic sampling by convenience; the results obtained show that this methodology had a positive impact on the learning of mathematics by raising enthusiasm, interest, understanding of concepts and cognitive skills in students significantly improving their mathematical skills.